The End of Museum Age - Notes on a New Profession - Šola, Tomislav (2008)
The lecture presented the general theory of heritage and focused on 3C institutions, including museums, creation of a strong profession throught the existance of good theory and practice. It also brought a critical view on the current state and proposed new perspectives in the heritage sector.